An epidemiological study of prevalence of hypertension and its risk factors in a rural community of Nellore, Andhra Pradesh, India - Singh, Manoj Kumar; Singamsetty, Bhaskar; Kandati, Jithendra (International Journal Of Community Medicine And Public Health, 2016)
Background: Hypertension [HTN] is responsible for 57% of stroke deaths and 24% of coronary heart disease [CHD] deaths in India. As per the statistics of Directorate General of Health Services, Ministry of Health and Family Welfare, Government of India, the overall prevalence of hypertension in India by 2020 will be 159.46/1000 population. Hypertension will be the major cause of death and disability by the end of 2020. The prevalence of hypertension is increasing in both rural and urban communities. The objectives of the study were to assess the prevalence of hypertension and its associate risk factors in a rural population. Methods: A cross sectional study was conducted by the Department of community medicine in the rural field practice area of a Medical college of Nellore from October 2013 to September 2015. The socio demographic variables and risk factors were obtained by interviewing the subjects in the study and collected in a predesigned questionnaire sheet. The sample size was calculated by prevalence of HTN in previous studies and 1025 subjects were included. The blood pressure was assessed and classified using recent JNC 7 and WHO criteria to grade hypertension. Results: In the study the prevalence of pre-hypertension was 42.63% (437 subjects), stage-I hypertension was 26.15% (268 subjects) and stage-II hypertension was 10.34%. The peak age of prevalence of HTN in both males and females was 60-69 years. Significant association was observed between age, low socio economic index, high salt intake (>10gms/day)) with hypertension. A linear trend of association was seen with tobacco and alcohol use, obesity (BMI>25) and waist-hip ratio more than the cut-off value (p value<0.005). Conclusions: Indian health system is challenged with increasing prevalence of non-communicable diseases and HTN being one of the major. Prioritization of population based prevention approaches requiring multi sectoral actions and evidence based clinical approaches focusing on early detection and treatment can provide benefit to population health. To increase the awareness on hypertension, information about prevention and control of hypertension can be incorporated in the information education and communication (IEC) components of all national programmes. This can complement overall efforts to increase societal awareness through other approaches.